Dyslipidemia in HIV-infected individuals - Sprinz, Eduardo (2010)
Metabolic complications continue to play a major role in the management of HIV infection. Dyslipidemia associated with HIV infection and with the use of combined antiretroviral therapy includes elevations in triglycerides, reduced high-density cholesterol, and variable increases in low-density and total cholesterol. The association between dyslipidemia and specifi c antiretroviral agents has been underscored. Multiple pathogenic mechanisms by which HIV and antiretroviral agents lead to dyslipidemia have been hypothesized, but they are still controversial. The potential clinical and pathological consequences of HIV-associated hyperlipidemia are not completely known, but several studies reported an increased risk of coronary artery disease in HIV-positive individuals receiving combined antiretroviral therapy. HIV-infected persons who have hyperlipidemia should be managed similarly to those without HIV infection in accordance with the National Cholesterol Education Program. Life style changes are the primary target. Statins and fi brates and/or modifi cation in antiretroviral therapy are possible approaches to this problem.